2002
DOI: 10.1016/s0030-4018(02)01447-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of energy relaxation rates near metal-coated dielectric cylinders

Abstract: The electromagnetic modes and their field distributions are evaluated for a dielectric cylindrical structure embedded in another dielectric, with a thin metallic film at the cylinder/dielectric interface. These modes provide energy relaxation channels for excited dipole emitters located inside or outside the cylinder. Significantly, we find that the emission rate is sensitive to the magnitude of the electron density of the metallic film coating. For typical parameter values, we find large enhancements of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although the decay emission of atoms in dielectric waveguides has been investigated [8], the atomic motion neither with steady state nor dynamical aspects optical forces in this structure have been reported before. Work along these lines is now in progress and the results will be reported in due course.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the decay emission of atoms in dielectric waveguides has been investigated [8], the atomic motion neither with steady state nor dynamical aspects optical forces in this structure have been reported before. Work along these lines is now in progress and the results will be reported in due course.…”
Section: Resultsmentioning
confidence: 94%
“…An evanescent mode pattern of guiding process a long hollow cylindrical waveguide has been suggested and the success was achieved in controlling atomic motion inside the submicron dimensions regime [6,8]. Normally the mechanisms * e-mail: alawfi99@hotmail.com of the atomic motion in light are controlled by the optical Bloch equations and they are solved in the steady state [212], to illustrate the mean optical forces for a two-and three-level atom.…”
Section: Introductionmentioning
confidence: 99%
“…The theory considering such features should additionally accommodate the first type of the atom waveguide, namely, the evanescent mode guides which can now have a novel feature, nanoscale dimensions. Although the emission decay for the atoms in the dielectric waveguides has already been investigated [21], the details of the JCM for the two-level atoms and its dynamics, along the lines discussed in this study, have not yet been reported. The work along these lines is now in progress.…”
Section: Discussionmentioning
confidence: 99%
“…3 as a dependence on the gt parameter for different detuning values 21  . The field is described by the coherent state with the Poisson distribution at the centre 20   .…”
Section: Dynamics Of the Jaynes-cummings Modelmentioning
confidence: 99%
“…The cylindrical geometries are already known to have generated particular interest for their usefulness not just as electromagnetic waveguides, but also as atom guides, where the guiding mechanism is governed mainly by the excited cavity modes. It is envisioned that the understanding of atom guides at such a small scale would lead to much desirable advances in atom lithography, which in turn should facilitate atomic physics research [121].…”
Section: Fig 2: (Color Online)mentioning
confidence: 99%